2009
DOI: 10.1111/j.1440-1746.2009.06046.x
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 monoclonal antibody blockade suppresses dextran‐sulfate‐sodium‐induced colitis in mice

Abstract: Blocking TLR4 by TLR4mAb can prevent the development of DSS-induced colitis through the TLR4-P38MAPK-c-jun pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 22 publications
3
24
0
Order By: Relevance
“…Trauma-induced TLR4 signaling in enterocytes leads to intestinal inflammation. We (23,43) and others (11,18,22,30,46) have recently demonstrated that small intestinal epithelial cells express TLR4 and that TLR4 activation within enterocytes leads to epithelial barrier disruption. On the basis of this prior work and in view of the findings of Fig.…”
Section: Remote Trauma Leads To Tlr4 Activation In the Intestinal Mucmentioning
confidence: 98%
“…Trauma-induced TLR4 signaling in enterocytes leads to intestinal inflammation. We (23,43) and others (11,18,22,30,46) have recently demonstrated that small intestinal epithelial cells express TLR4 and that TLR4 activation within enterocytes leads to epithelial barrier disruption. On the basis of this prior work and in view of the findings of Fig.…”
Section: Remote Trauma Leads To Tlr4 Activation In the Intestinal Mucmentioning
confidence: 98%
“…Inflammatory bowel disease has been associated with an increase in TLR4 activation (11), and therefore, we determined if feces from an IBD mouse model were altered in their capacity to activate TLR4 (Fig. 6A).…”
Section: Figmentioning
confidence: 99%
“…However, the mechanisms by which the host protects intestinal tissues from LPS exposure are impaired in certain forms of inflammatory bowel disease (IBD). For example, anti-TLR4 antibodies have been shown to reduce intestinal damage in dextran sodium sulfate (DSS)-treated mice (11), consistent with a significant increase in water-soluble pattern recognition receptor ligands in the feces of DSS-treated mice, such as the LPS receptor TLR4 (12). Similarly, in humans, individuals with Crohn's disease have increased circulating levels of MD-2, a key LPS coreceptor for TLR4 which results in significantly increased TLR4-dependent intestinal epithelial cell responses in vitro (13).…”
mentioning
confidence: 99%
“…In addition, TLR4 is indicated to be linked with MAPK pathway in IBD. TLR4 monoclonal antibody (TLR4mAb) ameliorates DSS-induced colitis via suppression of p38 MAPK pathway (21). TLR4 ligand LPS caused significant phosphorylation (activation) of MAPK in intestinal mucosal enterochromaffin cells isolated from Crohn's colitis patients (18).…”
mentioning
confidence: 99%